Penegakan HAM: Penyelesaian dan analisis pelanggaran ham terhadap masyarakat kecil di Indonesia - Katriya, cinta (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) are fundamental rights inherent in every human being from birth and cannot be revoked by anyone. In practice, human rights violations still frequently occur in Indonesia, particularly against small communities such as farmers, laborers, fishermen, indigenous peoples, and other economically disadvantaged groups. They are often victims of injustice due to abuse of power, social discrimination, forced evictions, labor exploitation, and weak legal protection. This article aims to analyze the forms of human rights violations against small communities in Indonesia and efforts to resolve them through legal, social, and public policy approaches. The method used is a literature study by examining laws and regulations, scientific journals, and various real-life cases that have occurred in Indonesia. The results of the study indicate that resolving human rights violations requires not only firm law enforcement but also the state's support for vulnerable groups through fair and participatory policies.